Can The Social Mission Model Improve the Students’ Interest? - Mar'atus Sholikah; Sutirman Sutirman; Febrika Yogie Hermanto (Faculty of Economics, State University of Jakarta., 2020)
This study aims to determine the effectiveness of entrepreneurship learning models based on social missions to advance entrepreneurial interest in vocational high school students. Experimental research use as a method, with 72 students participating in Class XII of SMK Negeri 1 Kudus. Data collection using questionnaires and learning outcomes. Data analysis using ANOVA and Scheffe test. The results showed that student learning outcomes with social mission learning models and conventional learning models have differences, where the social mission learning model is more useful to improve student learning outcomes and entrepreneurial interest. More than that, the social mission-based entrepreneurship learning model is needed in the curriculum. Entrepreneurship training through social mission will prepare students to become entrepreneurs, in addition to being more concerned about the environment and society. Future research needs to focus more on studying entrepreneurship learning curricula in vocational high schools.